Multimorbidity and Sleep Patterns among Adults in a Peruvian Semi-Urban Area - Méndez-Flores, Jhonatan J.; Marroquín-Cosar, Ruth E.; Bernabé-Ortiz, Antonio (Sleep Science, 2023)
Objective To assess if the duration and quality of sleep vary due to the presence of multimorbidity.Materials and Methods We performed a secondary analysis using data from a population-based study involving adult subjects aged between 30 and 69 years residing in a semi-urban area of Tumbes, Peru. The duration (normal, short or prolonged) and quality (good or poor) of sleep were our outcome variables, whereas the exposure was multimorbidity (two or more chronic conditions). Crude and adjusted Poisson regression models were built to assess the association of interest, and prevalence ratios (PRs) and 95% confidence intervals (95%CIs) were reported.Results We analyzed data from 1,607 subjects with a mean age of 48.2 (standard deviation [SD]: ± 10.6) years, 809 (50.3%) of whom were women. Multimorbidity was present in 634 (39.5%; 95%CI: 37.1–41.9%) subjects, and 193 (12.1%; 95%CI: 10.5–13.7%) were short sleepers, 131 (8.2%; 95%CI: 6.9–9.6%) were long sleepers, and 312 (19.5%; 95%CI: 17.5–21.5%) had poor sleep quality. In the multivariable model, multimorbidity was associated with prolonged sleep duration (PR = 1.45; 95%CI: 1.03–2.04) and poor sleep quality (PR = 2.04; 95%CI: 1.65–2.52).Conclusions Multimorbidity was associated with prolonged, but not short, sleep duration, as well as with poor sleep quality. Our results suggest the need of assessing sleep patterns among adults with multimorbidity.
Keywords: sleep; sleep hygiene; chronic disease; multiple chronic conditions